Office Administration Students Understanding of the Use of Standard Language - Anggi Karya Ningpasti; Ayu Swandana; Maulida Putri Lbs; Sharani Nafisha; Siti Oktavia Purba (Outline Publisher, 2025)
Standard language is a form of language that adheres to grammatical rules, spelling, and official vocabulary regulated in the Indonesian Spelling General Guidelines (PUEBI) as well as other language regulations. In the field of office administration, the use of standard language is essential because it directly relates to professionalism, credibility, and the effectiveness of communication in both official documents and oral communication. This study aims to examine office administration students’ understanding of standard language use in academic and professional contexts. The research method employed literature studies and observation of students’ coursework documents. The results show that although students understand the concept of standard language, its application is still inconsistent. Errors often occur in spelling, word choice, and sentence structure. The main factors behind the weak application of standard language include daily communication habits that tend to use non-standard language, the influence of social media, and the lack of practice in preparing official documents. Therefore, practical-based learning that emphasizes intensive training in writing formal documents is needed to improve the standard language proficiency of office administration students.